Peranan Masyarakat Dalam Meningkatkan Kualitas Lingkungan di Kelurahan Berngam Kecamatan Binjai Kota - Istiawati, Sri; S, Saniah; Fachrudin, Khaira Rizfia; Nasution, M. Hafis Akbar; Hans, Nickytha Linch De (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Some of the causes of deviations from spatial planning in cases of floods and landslides are the still weak public awareness of the importance of environmental quality, the weak ability to supervise and control development, both by the government and the community. The law in our country is not yet firm, and the spirit and mechanism of cooperation between development actors and the community have not yet been created in realizing synergistic development. The case of the lack of understanding of the Berngam Village community in Binjai City is also a factor in the decline in environmental quality. In conditions like this, the Binjai City government must realize the importance of socializing the material stipulated in the Spatial Planning product to the community, especially regarding improving environmental quality. This is intended so that the community can understand the importance of improving environmental quality. Seeing the limitations of the Binjai City government, the city community is expected to play an active role in developing alternative forms of urban land provision, such as the use of housing and settlement land, green open spaces, protected areas and so on that concern the interests of the community in general.